Analysing How Brands Use Activism in Advertising Campaigns to Challenge Gender Stereotypes in a South African Context. - Miza, Zuziwe (The IIE, 2022)
The portrayal of women in advertising is filled with stereotypes about who women are and what their roles should be in society. These stereotypes in advertising are reinforced through regular exposures and then embraced by individuals as the norm. The aforesaid generalisations can be negative, confining, and degrading, affecting how women perceive themselves and how they’re perceived by others. Therefore, the identified problem is that women are still being misrepresented in advertisments forcing them to live according to the deemed gender stereotypes. The study will further provide insight into how women are affected by gender stereotypes in advertising and how brands can play their part in influencing a change by using activist advertising. This mixed-method study unpacks and discusses the relevant qualitative and quantitative data collection methods which informed the identified findings. The main finding identified was that brand activism can influence a societal change, if authentically implemented by a brand however, though a brand may be steadfast in its activism, consumers don’t forget the wrong doings they may have been challenged with in the past. Therefore, brands need to make active strides in reassuring its consumers of the progress they are making in remedying the wrongs.
Keywords: Stereotyping; Brand awareness